2012
DOI: 10.1590/s1806-99592012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of plant growth promoting rhizobacteria in facilitating lead and nutrient uptake by little seed canary grass

Abstract: -(Effectiveness of plant growth promoting rhizobacteria in facilitating lead and nutrient uptake by little seed canary grass). We investigated the effectiveness of Nitroxin inoculation on lead (Pb) and nutrient uptakes by little seed canary grass. The factors tested included inoculation (or not) with Nitroxin and different soil concentrations of Pb (0, 200, 400 and 800 mgPb kg -1 soil). Increasing soil concentrations of Pb decreased stem, leaf and root dry weights. Shoot phosphorus concentrations increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In this regard, Zaefarian et al (2012) investigated the effectiveness of PGPR in the facilitation of Pb and nutrient uptake by littleseed canarygrass, reporting that the Pb TF value was >1 in the inoculated treatments with in the in the soil Pb concentration range of 200-400 mg/kg. However, the findings of the mentioned research indicated that in the Pb-polluted soil (> 800 mg/kg), the TF value was less than one even in the inoculated treatments [30]. Despite the contradictory reports regarding the effects of Pb toxicity on the plants Pb TF value [31,32], most of the findings have indicated that PGPG and AMF inoculation could reduce abiotic stress, such as heavy metal toxicity [33].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard, Zaefarian et al (2012) investigated the effectiveness of PGPR in the facilitation of Pb and nutrient uptake by littleseed canarygrass, reporting that the Pb TF value was >1 in the inoculated treatments with in the in the soil Pb concentration range of 200-400 mg/kg. However, the findings of the mentioned research indicated that in the Pb-polluted soil (> 800 mg/kg), the TF value was less than one even in the inoculated treatments [30]. Despite the contradictory reports regarding the effects of Pb toxicity on the plants Pb TF value [31,32], most of the findings have indicated that PGPG and AMF inoculation could reduce abiotic stress, such as heavy metal toxicity [33].…”
Section: Resultsmentioning
confidence: 97%
“…According to the study by Zaefarian et al (2012) high concentrations of Pb in soil could significantly reduce the nitrogen content of plant roots [30]. In addition, rhizobacteria were reported to produce various growthpromoting hormones (e.g., auxins, gibberellins, and B vitamins), which stimulated root exudate production [30].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our results demonstrated that inoculation of plants with efficient and resistant PGPR, particulary with I1, I5 and I9, markedly affected plant agronomic parameters under Pb stress, most likely by alleviating Pb toxicity (Zaefarian et al . ), and increased plant biomass as compared to treatment without inoculation. The improvement in growth parameters in plants inoculated with I1, I5 and I9 could be due to the N fixation ability of R. leguminosarum (M5) and the important IAA production of Luteibacter sp., demonstrating the potential of these PGPR in producing growth‐promoting substances in L. sativus .…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, Pb can directly affect cell elongation by inhibiting cell wall enzymes and the plasmalemma ATPase by dampening electron translocation during photosynthesis and respiration, thus reducing plant growth (Zaefarian et al . ). It is interesting to note that roots were more infuenced by Pb stress than aerial plant parts, which might be due to the higher accumulation of Pb in L. sativus roots (Brunet et al .…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have demonstrated that Pb 2+ not only can affect physiological and biochemical reactions in plants, but can also induce numerous adverse responses in animals and humans [4][5][6][7]. The molecular mechanism of Pb toxicity has attracted a lot of attention in the fi eld of abiotic stress research.…”
Section: Introductionmentioning
confidence: 99%